Doenças cardiovasculares ateroscleróticas, dislipidemias, hipertensão, obesidade e diabetes melito em população da área metropolitana da região Sudeste do Brasil: II - Dislipidemias Atherosclerotic cardiovascular disease, lipemic disorders, hypertension, obesity and diabetes millitus in the population of a metropolitan area of southeastern Brazil. II - Lipemic disorders - Ignez Salas Martins; Maria de Fátima Nunes Marucci; Ana Maria Cervato; Eliza Tieko Okani; Rosa Nilda Mazzilli; Mônica Inês Casajus (Universidade de São Paulo, 1996)
Objetivou-se caracterizar a prevalência de dislipidemias e outros fatores de risco em grupos populacionais, do Município de Cotia, "Área Metropolitana" de São Paulo, Brasil. Os grupos populacionais foram definidos a partir de características socioeconômicas e de localizaço geográfica no Município. Foram abordados os seguintes fatores de risco: hábitos alimentares aterogênicos (consumo de proteínas de origem animal, gorduras saturadas e de colesterol), tabagismo, etilismo, sedentarismo, dislipidemias, obesidade, hipertensão e diabetes melito. Os resultados encontrados foram os seguintes: 1 - O número médio de fatores de risco foi significantemente maior nos homens (p<0,01), comparado às mulheres, para as faixas etárias menores de 50 anos; entre 50-55 anos as médias se igualam para ambos os sexos, atingindo o valor máximo aos 60 anos com redução acentuada após essa idade, no que se refere aos homens e apresentando um aumento constante e gradativo nas mulheres; 2 - O número médio de fatores de risco aumentam com a idade (p<0,01), para ambos os sexos; 3 - As prevalências de hipercolesteolemia de "alto risco" mais hipertrigliceridemia foram significantemente maiores nas classes de maior nível socioeconômicos; 4 - Os perfis lipêmicos associados às dislipidemias demonstraram que raramente os desarranjos lipêmicos ocorreram com um constituinte isoladamente; 5 - Somando-se as hipercolesterolemias de "alto risco", as "limítrofes acompanhadas de dois ou mais fatores de risco" e as hipertrigliceridemias têm-se que 39,2% dos homens e 32,8% das mulheres, ou seja, 35,4% da população amostrada necessitaria de imediata intervenção clínico-educativa. This study has sought to characterize the prevalence of lipemic disorders and other risk factors of atheroschlerotic cardiovascular disease in population groups of Cotia county in Greater S. Paulo, Brazil. The population groups were defined on the basis of socio-economic characteristics and geographical location within the county such as provided elements for the delimitation of the "study areas". A sample representative of each of these areas was taken, constituting in all 1,041 individuals. The data related to eating habits were collected from a sub-sample of 568 people. The lipemic disorders diagnosed were as follows: high risk hypercholesterolemias with values 240mg/dl for total cholesterol and 160mg/dl for LDL-cholesterol; borderline risk hypercholesterolemias with values > 200mg/dl and > 130mg/dl for total cholesterol and LDL-cholesterol respectively; hypertriglyceridemia, with values 250mg/dl. The following risk factors were included: atherogenic eating habits (consumption of proteins of animal origin, saturated fats and cholesterol), smoking, drinking, sedentary life style, obesity (IMC >25kg/m²), hypertension (140/90mmHg) and diabetes mellitus (glycemia>120mg/dl). The results found were the following: 1- the average number of risk factors was significant by greater among men than among women, for the age groups below 50 years of age (p<0.01); between 50 and 55 years of age they were equal for the two groups, reaching their greatest value at 60 years of age with a sharp reduction after this latter age as regard the men but presenting a constant gradual increase for the women; 2 - the average number of risk factors increased with age for both sexes (p<0.01); 3 - the prevalences of high risk hypercholesterolemias together with hypertriglyceridemia ( > or = 250mg/dl) were significantly greater in the classes of higher socio-economic level; 4 - the lipemic profile associated with lipemic disorders show that these latter rarely occur with just one constituent in isolation; 5 - when the high-risk hypercolesterolemias are added to the borderline cases accompanied by two or more risk factors and hypertriglyceridemia they give a total of 39.2% of men and 32.8% of women, that is to say, 35.4% of the sample need immediate clinical-educational intervention.